CONSTRUCTION ANALYSIS OF SOLAR PANEL FOUNDATION ON THE SURFACE OF DAM WATER BODY WITH DAM SLOPE : (Case Study: Jatibarang Dam Solar Power Plant - Semarang) - Puntodewo, Setyasto; Oetomo, Wateno; Darjanto, Helmy (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
Indonesia's potential solar panel renewable energy capacity is 207.8 GW, currently only 0.135 GW has been realized or 0.02% has only been achieved. The development is still very broad and far ahead. The best place for a PLTS (Solar Power Plant) location is in the dam area. Why? The dam has a very large area and is owned by the government. This paper investigates the comparison of the cost and time of implementing PLTS foundation construction at the location of the Dam Slope (Landed) and on the Surface of the Dam Water Body (Floating). The research was conducted based on a case study of the application of PLTS in the Jatibarang Dam. Where in 2017 the construction of PLTS has been realized at the location of the Dam Slope. The PLTS Floating model was developed with a design simulation based on real data at the same dam location. The cost and time indicators for both Landed and Floating foundation models are then calculated and compared. From the analysis results, in terms of costs, the application of the PLTS Floating foundation is 41% higher than the foundation on the slopes. But in time 31% faster than the Slope foundation. By knowing the cost and time comparison between the two PLTS laying models, the aim is to design a PLTS development strategy for the Dam area based on the most optimal considerations.